2010
DOI: 10.1074/jbc.m109.024190
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-activated Calpain-2 Is a Mediator of Beta Cell Dysfunction and Apoptosis in Type 2 Diabetes

Abstract: The islet in type 2 diabetes (T2DM) and the brain in neurodegenerative diseases share progressive cell dysfunction, increased apoptosis, and accumulation of locally expressed amyloidogenic proteins (islet amyloid polypeptide (IAPP) in T2DM). Excessive activation of the Ca 2؉ -sensitive protease calpain-2 has been implicated as a mediator of oligomer-induced cell death and dysfunction in neurodegenerative diseases. To establish if human IAPP toxicity is mediated by a comparable mechanism, we overexpressed human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 56 publications
3
84
0
Order By: Relevance
“…To further investigate the role of p62 accumulation in b-cells of h-IAPP transgenic rodents, we used the INS 832/13 (rat insulinoma cell line) cells transduced with adenoviruses expressing h-IAPP or the non-amyloidogenic and non-toxic r-IAPP for comparable load of protein. 20 Cells transduced with h-IAPP exhibited a B5-fold increase in LC3-II levels after 36 and 48 h (Po0.01), suggesting either an induction of autophagy or a decrease in autophagosome clearance (Figure 4), comparable to that reported above in vivo. In cells transduced with r-IAPP, LC3-II levels were also increased at 48 h (3.2 ± 0.3-fold, Po0.001), but to a much lesser extent than in cells transduced with h-IAPP (Figure 4).…”
Section: Figuresupporting
confidence: 66%
See 1 more Smart Citation
“…To further investigate the role of p62 accumulation in b-cells of h-IAPP transgenic rodents, we used the INS 832/13 (rat insulinoma cell line) cells transduced with adenoviruses expressing h-IAPP or the non-amyloidogenic and non-toxic r-IAPP for comparable load of protein. 20 Cells transduced with h-IAPP exhibited a B5-fold increase in LC3-II levels after 36 and 48 h (Po0.01), suggesting either an induction of autophagy or a decrease in autophagosome clearance (Figure 4), comparable to that reported above in vivo. In cells transduced with r-IAPP, LC3-II levels were also increased at 48 h (3.2 ± 0.3-fold, Po0.001), but to a much lesser extent than in cells transduced with h-IAPP (Figure 4).…”
Section: Figuresupporting
confidence: 66%
“…The complementary cDNA encoding the full-length human and rat preproIAPP were used as templates to generate the human and rat IAPP adenoviruses, as described previously. 20 Recombinant adenovirus expressing human and rat preproIAPP (h-IAPP and r-IAPP, respectively) were produced and purified according to the manufacturer's instructions (Clontech, Palo Alto, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To test the hypothesis that p62 is required for IAPP degradation by autophagy, we evaluated the interaction between IAPP and p62 in INS 832/13 cells transduced with adenoviruses expressing h-IAPP or the nonamyloidogenic and nontoxic r-IAPP (used as a control for comparable burden of protein expression [Supplemental Figure 6A] as previously published; refs. [17][18][19]. In all 3 conditions (control and r-IAPP-and h-IAPP-transduced cells), IAPP immunoprecipitated with p62 ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…1A). Previous studies have shown that calpain 2 activation is regulated on the ER membrane and it plays a role in ER stress-induced apoptosis and β cell death (20,(22)(23)(24), which prompted us to study the role of WFS2 in calpain 2 activation.…”
Section: Significancementioning
confidence: 99%